Research Universities in the Framework of Regional Innovation Ecosystem: The Case of Austin, Texas - David Gibson; John Butler (Foresight and STI Governance, 2013)
Based on the case of the University of Texas at Austin, the authors provide a model of knowledge-based regional development that enables leadership and international competitiveness. In the framework of this model, University of Texas is regarded as a core of a regional innovation system. In addition to the traditional objectives of performing research and education, universities are increasingly tasked with the third mission of transferring and commercializing university-based R&D to stimulate economic development. While responding to growing industry needs and efficiently interrelating with industries and governments, universities shape a unique entrepreneurial environment that foster development of the regional innovation ecosystem. The university has a direct impact on the regional innovation ecosystem development and is also impacted by feedback loops from the ecosystem. This enables reinforcement of the university’s potential.The case of Austin shows that its successful transformation from a university town to a fast-growing, globally competitive hi-tech hotspot has occurred mainly owing to visionary influencers rather to institutional excellence in science, industry or governance. Their ability to make bolddecisions, connect and leverage otherwise unconnected and perhaps competingsectorsin the framework oflarge-scale projects, generatea creativeenvironment forproductive partnershipsand achievesynergyled to theinstitutional and organizationalchange.The model here is based on so-called «Technopolis Wheel» consisting of seven sectors: the research university; large and small entrepreneurial firms; federal, state and local government; and support groups (business associations, chamber of commerce, etc.). The paper characterizes in detail the role of each sector in the transformation of Austin region.